Endothelial Cell Count in Eye Bank Corneal Grafts: Impact of Death Cause and Donor Diseases. (3rd April 2018) - Filev, Filip; Hellwinkel, Olaf J. C.; Eddy, Mau-Thek; Linke, Stephan J.; Wulff, Birgit
ABSTRACT: Purpose : The purpose of this study is to analyze the impact of death causes and documented donor diseases on initial endothelial cell counts (after retrieval) and the development of corneal graft endothelia during organ culture. Methods : The retrospective statistic analyses was conducted on a data set of 10, 185 human corneas prepared at the Hamburg Eye Bank. Results : Although we observed that death by gunshot trauma or alcoholism seems to be associated with marginally higher endothelium cell counts (independently from donor age), we could prove that only donor age is a relevant predictive parameter for the initial cell-density of the endothelium and its development in vitro. Conclusion : We conclude that an extension of prospective quality parameters for donor selection additional to donor age (such as individual causes of death) is not necessary.